Family companions' involvement during pre-surgical consent visits for major cancer surgery and its relationship to visit communication and satisfaction. Issue 6 (June 2018) - Isenberg, Sarina R.; Aslakson, Rebecca A.; Dionne-Odom, James N.; Clegg Smith, Katherine; Singh, Sarabdeep; Larson, Susan; Bridges, John F.P.; Smith, Thomas J.; Wolff, Jennifer L.; Roter, Debra L.
Highlights: Companion communication was largely emotional and facilitative. Companion presence was associated with a 41% increase in surgeons medical information. Companion presence was associated with 45% less patient psychosocial disclosure. Companions presence was associated with 23% lower levels of patient-centeredness. Companion presence did not significantly impact patient nor surgeon satisfaction. Abstract: Objective: To examine the association between family companion presence during pre-surgical visits to discuss major cancer surgery and patient-provider communication and satisfaction. Methods: Secondary analysis of 61 pre-surgical visit recordings with eight surgical oncologists at an academic tertiary care hospital using the Roter Interaction Analysis System (RIAS). Surgeons, patients, and companions completed post-visit satisfaction questionnaires. Poisson and logistic regression models assessed differences in communication and satisfaction when companions were present vs. absent. Results: There were 46 visits (75%) in which companions were present, and 15 (25%) in which companions were absent. Companion communication was largely emotional and facilitative, as measured by RIAS. Companion presence was associated with more surgeon talk (IRR 1.29, p = 0.006), and medical information-giving (IRR 1.41, p = 0.001). Companion presence was associated with less disclosure of lifestyle/psychosocial topics by patients (IRR 0.55, p = 0.037). In adjusted analyses, companions' presence was associated with lower levels of patient-centeredness (IRR 0.77, p 0.004). There were no differences in patient or surgeon satisfaction based on companion presence. Conclusion: Companions' presence during pre-surgical visits was associated with patient-surgeon communication but was not associated with patient or surgeon satisfaction. Practice implications: Future work is needed to develop interventions to enhance patient-companion-provider interactions in this setting.